ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE FULL COSTING DAN VARIABLE COSTING SEBAGAI DASAR PENETAPAN HARGA JUAL PRODUK - Nafisah, Nailatun; Dientri, A. Manaf; Darmayanti, Novi; Winarno, Wahyu; Hairudin, Hairudin (J-MACC : journal of management and accounting, 2021)
The calculation of the cost of production is very important for manufacturing companies considering that one of the benefits of the cost of production is to determine the selling price of the product. There are two methods in determining the cost of production, namely the full costing method and the variable costing method. The purpose of this study is to find out how to calculate the cost of production using the full costing method and variable costing to determine the selling price on CV Starnine. The method in this research is quantitative descriptive method. The research data collection technique is by observation, interview and documentation. The results showed that there were weaknesses in the calculation of the company's cost of production. Based on the comparison between the full costing method and the variable costing method of the company's cost of production, the cost of production according to the full costing method has a nominal value that is higher than the variable costing method. This is because in the calculation of the cost of production the full costing method takes into account all costs incurred by the company while producing both variable and fixed products.